2014
DOI: 10.1107/s1399004714020938
|View full text |Cite
|
Sign up to set email alerts
|

Alliin is a suicide substrate ofCitrobacter freundiimethionine γ-lyase: structural bases of inactivation of the enzyme

Abstract: The interaction of Citrobacter freundii methionine γ-lyase (MGL) and the mutant form in which Cys115 is replaced by Ala (MGL C115A) with the nonprotein amino acid (2R)-2-amino-3-[(S)-prop-2-enylsulfinyl]propanoic acid (alliin) was investigated. It was found that MGL catalyzes the β-elimination reaction of alliin to form 2-propenethiosulfinate (allicin), pyruvate and ammonia. The β-elimination reaction of alliin is followed by the inactivation and modification of SH groups of the wild-type and mutant enzymes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
(57 reference statements)
1
20
0
1
Order By: Relevance
“…Therefore, it is one of the hotspot research areas in the field of cancer to explore new therapy for regulating the cellular mechanisms and inducing apoptosis to treat tumors and more and more studies are focusing on natural products. Allicin is a sulfur compound extracted from garlic bulbs [11,39]. The surveys of epidemiology show that allicin has an inhibition effect on many malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is one of the hotspot research areas in the field of cancer to explore new therapy for regulating the cellular mechanisms and inducing apoptosis to treat tumors and more and more studies are focusing on natural products. Allicin is a sulfur compound extracted from garlic bulbs [11,39]. The surveys of epidemiology show that allicin has an inhibition effect on many malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have showed that PLP‐dependent MGL (EC 4.4.1.11) from Citrobacter freundii catalyzes the β‐elimination reaction of alliin and other S‐substituted l ‐cysteine sulfoxides to form allicin or S‐alkylthiosulfinates:
…”
Section: Introductionmentioning
confidence: 99%
“…C. freundii MGL contains cysteine 115 residue in the active site . To avoid the observed 31% inactivation of the enzyme in the β‐elimination reaction of alliin , we prepared the mutant form of C. freundii MGL with the replacement of cysteine 115 by histidine. The replacement allowed us to obtain an effective catalyst for the production of thiosulfinates .…”
Section: Introductionmentioning
confidence: 99%
“…In C. freundii, among the seven cysteine residues present in the amino acid sequence, two are highly reactive to modification by DTNB. According to crystallographic data, C4 and C115 are the most plausible candidates . In C. novyi MGL, we determined that one SH group reacts rapidly with DTNB under native conditions and three SH groups react with DTNB in 6 M guanidine hydrochloride, as expected on the basis of the amino acid sequence.…”
Section: Resultsmentioning
confidence: 81%
“…Recently, we provided evidence for the cytotoxicity of MGL from C. sporogenes, C. tetani, and Citrobacter freundii MGL using K562, PC-3, LnCap, MCF7, SKOV-3, and L5178y tumor cell lines (9). We also reported the capability of MGL to catalyze the formation of the potent antibacterial agent allicin or Salkylthiosulfinates from substrate analogues, such as alliin and S-substituted L-cysteine sulfoxides (10,11).…”
Section: Introductionmentioning
confidence: 94%